Effect of different irrigation solutions and calcium hydroxide on bacterial LPS - Tanomaru, JMG; Leonardo, M. R.; Tanomaru, M.; Bonetti, I; Silva, LAB (Blackwell Publishing, 2003)
Aim To evaluate the effect of biomechanical preparation with different irrigating solutions and calcium hydroxide dressing in dog root canals containing bacterial endotoxin (lipopolysaccharides; LPS).Methodology One hundred and forty premolar roots from seven dogs were filled with Escherichia coli LPS for 10 days (three roots were lost during histological processing). The following irrigating solutions were used for biomechanical preparation: 1% (group I, n = 20), 2.5% (group II, n = 19) and 5% sodium hypochlorite (group III, n = 19), 2% chlorhexidine digluconate (group IV, n = 20) and physiological saline solution (group V, n = 19). In group VI (n = 20), the LPS solution was maintained in the root canal during the entire experiment and in group VII (n = 20), after biomechanical preparation with saline solution, the root canals were filled with a calcium hydroxide dressing (Calen; control). After 60 days, the animals were sacrificed and the following parameters of periapical disease were evaluated: (a) inflammatory infiltrate, (b) periodontal ligament thickness, (c) cementum resorption and (d) bone resorption. Scores were given and data were analysed statistically with the Kruskal-Wallis and Dunn tests (P < 0.05).Results Histopathological evaluation showed that groups I-VI had more inflammatory infiltrate, greater periodontal ligament thickening and greater cementum and bone resorption (P < 0.05) compared to group VII, which received the calcium hydroxide intracanal dressing.Conclusions Biomechanical preparation with the irrigating solutions did not inactivate the effects of the endotoxin but the calcium hydroxide intracanal dressing did appear to inactivate the effects induced by the endotoxin in vivo.
Keywords: calcium hydroxide; chlorhexidine; endodontics; endotoxin; sodium hypochlorite